Designing for the Base of the Pyramid By Patrick Whitney and Anjeli Kelkar. (December 2014) - Nussbaum, Bruce
<x xml:space="preserve">Abstract</x> Designing for complex systems is at the pioneering edge of the design field. Designing for the complex systems of the slums of India or Africa takes us even further. This piece by Patrick Whitney, dean of the Institute of Design (ID) at the Illinois Institute of Technology, and Anjali Kelkar, who was at that time a research associate at ID and now works for Steelcase, highlights how far we have come in creating methodologies of understanding for the field of design itself. One of the most important issues of design is social complexity. Products and services exist within deep cultural and social norms and networks. Designing without taking this context into account usually dooms the designer and the design. For over a decade now, Whitney has been leading an effort to create a systematic methodology of discovery and measurement of need and fulfillment, especially at The Base of the Pyramid. The framework is able to sift through the myriad of forces helping people poor to focus on one or two factors that can be improved and through their improvement, leverage the betterment of peoples' lives. In this article, we get a look at ID's research in India. It shows that lack of access to clean water and financial credit are two of the most important factors in keeping people poor. ID goes further and designs a new clean water delivery business model. It could service a critical need, as well as employ local people. ID has also designed a business model to provide credit to poor people at the bottom of the pyramid. Of course, this approach to design should be applied to the entire pyramid—bottom, middle, and top. The power of design needs to be applied throughout society in all societies.